PENGEMBANGAN POTENSI DESA WISATA UNTUK MENINGKATKAN PERTUMBUHAN EKONOMI DAN KEMAKMURAN MASYARAKAT DI DESA WISATA MERABU KABUPATEN BERAU - Endah Susanti (ECO-BUILD, 2025)
Tourism has adapted rapidly in various worlds, including Indonesia, and created significant harmonization for economic, social, and cultural uses. Since the change in the village's status forest (HD) in 2014, we hope it will become an opportunity for Merabu Village to increase the productivity of agriculture, livestock, and tourist destinations. The focus of this study is to explore the tourism potential of Merabu Village and how does it affect the economic growth and prosperity of the Merabu village community, especially after the covid-19 pandemic. We got data sets through interviews, and field observations of several informants who predominantly work as farmers. The trend of tourist visits every year is also increasing, and especially rural tourism managed by Kerima Puri. Since the beginning of the presence of domestic tourists and foreign tourists, there have been tour boat services that took them to the gate of Nya’deng Lake, homestays, food providers, and various traditional attractions (cultural festivals). As a rural tourism area, HD has a positive impact on local residents to be involved in rural tourism development. This finding also hopes for a real contribution from relevant parties to advance the rural tourism of Merabu Village.